An arrayed CRISPR screen of primary B cells reveals the essential elements of the antibody secretion pathway - Trezise, Stephanie; Kong, Isabella Y.; Hawkins, Edwin D.; Herold, Marco J.; Willis, Simon N.; Nutt, Stephen L. (Frontiers in Immunology, 2023)
Humoral immunity depends on the differentiation of B cells into antibody secreting cells (ASCs). Excess or inappropriate ASC differentiation can lead to antibody-mediated autoimmune diseases, while impaired differentiation results in immunodeficiency. We have used CRISPR/Cas9 technology in primary B cells to screen for regulators of terminal differentiation and antibody production. We identified several new positive (Sec61a1, Hspa5) and negative (Arhgef18, Pold1, Pax5, Ets1) regulators that impacted on the differentiation process. Other genes limited the proliferative capacity of activated B cells (Sumo2, Vcp, Selk). The largest number of genes identified in this screen (35) were required for antibody secretion. These included genes involved in endoplasmic reticulum-associated degradation and the unfolded protein response, as well as post-translational protein modifications. These genes represent weak links in the antibody-secretion pathway that are potential drug targets for antibody-mediated diseases, as well as candidates for genes whose mutation results in primary immune deficiency.